Lipoprotein(a) and stroke: a two-sample Mendelian randomization study - Huang, Yi; Zhang, Ruijie; Han, Liyuan; Wu, Yiwen; Deng, Xinpeng; Xu, Tianqi; Wu, Yuefei; Gao, Xiang; Zhou, Chenhui; Sun, Jie (Frontiers in Aging Neuroscience, 2023)
Background To evaluate the causal relationship between lipoprotein(a) Lp(a) and stroke risk. Method Adopting two grand scale genome-wide association study (GWAS) databases, the instrumental variables were selected on the basis that the genetic loci met the criteria of being independent of each other and closely related to Lp(a). Summary-level data for outcomes, ischemic stroke and its subtypes were acquired from the UK Biobank and MEGASTROKE consortium databases. Two-sample MR analyses were achieved using inverse variance-weighted (IVW) meta-analysis (primary analysis), weighted median analysis, and the MR Egger regression method. Multivariable-adjusted Cox regression models were also used for observational analysis. Result Genetically predicted Lp(a) was marginally related with higher odds of total stroke (odds ratio (OR) [95% confidence intervals (CI)]: 1.003 [1.001–1.006], p = 0.010), ischemic stroke (OR [95% CI]: 1.004[1.001–1.007], p = 0.004), and large-artery atherosclerotic stroke (OR [95% CI]: 1.012 [1.004–1.019], p = 0.002) when the IVW estimator was used on the MEGASTROKE data. The associations of Lp(a) with stroke and ischemic stroke were also remarkable in the primary analysis using the UK Biobank data. Higher Lp(a) levels were also related with increased total stroke and ischemic stroke risk in the observational research data in the UK Biobank database. Conclusion Genetically predicted higher Lp(a) perhaps rise the risk of total stroke, ischemic stroke, and large-artery atherosclerotic stroke.